2020
DOI: 10.1002/pol.20200151
|View full text |Cite
|
Sign up to set email alerts
|

Plasticization mechanism in polybenzimidazole membranes for organic solvent nanofiltration: Molecular insights from in situ FTIR spectroscopy

Abstract: Despite substantial research efforts being devoted to design polymer membranes for organic solvent nanofiltration (OSN) exhibiting enhanced plasticization resistance, detailed studies of membrane structural stability in chemically challenging environments are rare. This study sets forth a multiscale method, which combines in situ FTIR measurements in the transmission mode with sorption and transport measurements, to investigate the molecular mechanism of polymer plasticization upon exposure to organic species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This observations is in line with a previous report on PBI. 5 The XRD analysis revealed that the structure of the MPC membranes is dominated by amorphous characteristics (Fig. 2g).…”
Section: Metal-polymer Coordination-driven Membrane Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observations is in line with a previous report on PBI. 5 The XRD analysis revealed that the structure of the MPC membranes is dominated by amorphous characteristics (Fig. 2g).…”
Section: Metal-polymer Coordination-driven Membrane Constructionmentioning
confidence: 99%
“…Consequently, PBI has recently been explored for OSN. [1][2][3][4][5] Nevertheless, PBI membranes are not stable in harsh polar aprotic solvents without crosslinking.…”
Section: Introductionmentioning
confidence: 99%
“…However, in contrast to permeance, permeability is an intrinsic membrane material property and, as such, it should be used to develop structure-property correlations instead of permeance. 14,58,[60][61][62] Based on the solution-diffusion model, the permeability of species i is given by: 14,58 (1) = × where is the diffusion coefficient and is the sorption coefficient. The membrane selectivity is the ratio of the permeability of the components i-to-j, and can be deconvoluted into the sorption and diffusion selectivity as follows:…”
Section: Transport Mechanism In Membranesmentioning
confidence: 99%
“…The plasticization of polymer can reduce the interactions among polymer chains, increasing their mobility as a result. 38 Free volume theory is often employed to explain the plasticization mechanism. The larger the free volume, the better the mobility of polymer chain.…”
Section: Free Volume Of the Lead-containing Plexiglassmentioning
confidence: 99%